Are Beauty Brands Green or Green Washed? A Qualitative Study on Customers’ Perception (The International Research Journal of Management Science, 2024)
With growing awareness of environmental issues such as global warming and pollution, consumers are increasingly shifting towards green products. In response, beauty brands are promoting their products as sustainable. However, consumers have recently begun questioning the authenticity of these green claims. Drawing from behavioral reasoning theory (BRT), this paper investigates customers' perceptions of green beauty brands in Nepal. A qualitative approach using a convenience sampling technique was employed to reach eight beauty green consumers. Data were collected and analyzed by using semi-structured interviews and Braun and Clarke’s thematic analysis respectively. The authors explored the evaluation of green practices, perceived factors supporting green practices, and perceived challenges as overarching themes. Additionally, a new theme of greenwashing perception emerged from a lack of transparency, accountability, and third-party verification of green beauty brands. To the best of our knowledge, this is one of the earliest qualitative studies to explore green practices among beauty brands in Nepal.